Odpowiedzi

2009-11-29T21:05:35+01:00
( x + 5 )^ {2}=x2+25x2+25= 26x2+25
(x+6) ^{2} =x2+36x2+36= 37x2+36
(2x+2)^{2}=4x2+16x2+4= 20x2+4
(2x+3)^{3}=8x3+216x3+27= 224x3+27
(2x+4)^{2}=4x2+64x2+16= 68x2+16
(2x+6)^{2}=4x2+144x2+36= 148x2+36

reszty nie wiem
2009-11-29T21:16:13+01:00
(x+5)^{2}=x^2+2*x*5+5^2=x^2+10x+25
(x+6)^{2} =x^2+2*x*6+6^2=x^2+12x+36
(2x+2)^{2}=(2x)^2+2x*2*2+2^2=4x^2+8x+4
(2x+3)^{2}=(2x)^2+2*2x*3+3^2=4x^2+12x+9
(2x+4)^{2}=(2x)^2+2*2x*4+4^2=4x^2+16x+16

(x-2)^{2}=x^2-2*2*x+2^2=x^2-4x+4
(x-4)^{2}=x^2-2*4*x+4^2=x^2-8x+16
(x-5)^{2}=x^2-2*5*x+5^2=x^2-10x+25
(x-6)^{2}=x^2-2*6*x+6^2=x^2-12x+36

(2x-2)^{2}=(2x)^2-2*2*2x+2^2=4x^2-8x+4
(2x-4)^{2}=(2x)^2-2*4*2x+4^2=4x^2-16x+16
(2x-5)^{2}=(2x)^2-2*5*2x+5^2=4x^2-20x+25
(2x-6)^{2}=(2x)^2-2*6*2x+6^2=4x^2-24+36